Effect Of Soil Grain Size On The Oil Migration In The Capillary Fringe Zone - Lee, Zheng Xian (Universiti Sains Malaysia, 2019)
Widespread demand for petroleum had lead potential problems associated with underground storage tanks and oil pipelines. Over time, these pipelines and tanks can have corroded and developed leakages. LNAPL had the complex parameter to allow the LNAPL to move through the porous media under saturation condition, which is depressing the capillary fringe zone. Therefore, the capillary height or the depth to reach the capillary height is very important to be define as the depth is representing the location of the remediation work to be carry out. The main objective of this research is to determine the depression of the capillary fringe when encountered with diesel in different grain size of sand samples. The One-Dimensional Column Test had been carried out with the Image Analysis in order to determine the capillary fringe zone in the column apparatus. With the different colours’ toning, blue water and red diesel, the captured image is then processed by the MATLAB code to scale the toning. The darkest blue and red represented 100% saturation of water and diesel. By determine the highest level of 100% saturation of water, the capillary height can be figured out. In this research, the result showed that the smallest D10 value had the highest capillary height due to its largest adhesive force among sand particles. Besides that, the diesel poured into the sand samples and the depression of capillary fringe zone had been determined. The results showed the diesel can depress more capillary fringe zone in the smaller grain size of sand samples. This can be explained as capillary force is an equilibrium force of adhesive force and gravitational force based on Young-Laplace theory. The capillary force acting same direction as the gravitational force had pushed the diesel downward more easier in smaller grain size sand samples as they had the bigger capillary pressure to form the diesel plume in order to penetrate downward through the sand samples.